Optimalisasi Kader Lansia dalam Upaya Peningkatan Kualitas Hidup dan Self Care pada Lansia dengan Hipertensi di Desa Cepaka - Sherlyna Prihandhani, IGAA; Widiastuti, Putu; Trisna, Made Oktaviani Bulan (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2024)
Background: Hypertension is one of the causes of premature death because it is associated with the risk of cardiovascular disease. In Indonesia itself, the prevalence of hypertension is quite high, reaching 34.11% in the population over 18 years of age because it is related to the poor lifestyle of Indonesian people, such as eating daily food, rarely consuming fruits and vegetables that are rich in nutritional deficiencies, rarely exercising, smoking from an early age, frequently drinking alcoholic beverages, frequently experiencing severe stress, or hypertension sufferers who do not regularly take medication. Purpose : this training is an intervention effort towards self-care and quality of life for cadres in Cepaka Village with the hope of improving the quality of life for the elderly. Method : will be carried out face to face for one month in four meetings. The meeting consists of assessment activities before (pre test), lecture, video screening, distribution of booklets and assessment after (post test). Results: based on the pre-test results, the average was 67 and after the post-test the average participant score was 85, so that there was an increase in knowledge and an increase in the optimization of cadets in Cepaka Village. Conclusion: This PKM has been implemented by providing education through the delivery of material, and understanding of the material followed by participants. Participants consisted of elderly cadres from Cepaka Village.